Spectrum of Endocrine Dysfunction and Association With Disease Severity in Patients With COVID-19: Insights From a Cross-Sectional, Observational Study - Das, Liza; Dutta, Pinaki; Walia, Rama; Mukherjee, Soham; Suri, Vikas; Puri, Goverdhan Dutt; Mahajan, Varun; Malhotra, Pankaj; Chaudhary, Shakun; Gupta, Rahul; Jayant, Satyam Singh; Agrawal, Kanhaiya; et al. (Frontiers in Endocrinology, 2021)
Introduction: Evidence pertaining to new-onset endocrine dysfunction and identifying whether the quantum of this dysfunction is associated with the severity of disease in patients with COVID-19 is scarce. Patients and Methods: Consecutive patients enrolled at PGIMER Chandigarh, were stratified on the basis of disease severity as: group I (moderate-to-severe disease including oxygen saturation <94% on room air or those with comorbidities) (n=35) and group II (mild disease, with oxygen saturation >94% and without comorbidities) (n=49). Hypothalamo-pituitary-adrenal, thyroid, gonadal axes and lactotroph function were evaluated. Inflammatory and cell-injury markers were also analysed. Results: Patients in group I had higher prevalence of hypocortisolism (38.5 vs 6.8%, p=0.012), lower ACTH (16.3 vs 32.1pg/ml, p=0.234) and DHEAS (86.29 vs 117.8µg/dl, p= 0.086) as compared to group II. Low T3 syndrome was a universal finding, irrespective of disease severity. Sick euthyroid syndrome (apart from low T3 syndrome) (80.9 vs 73.1%, p= 0.046) and atypical thyroiditis (low T3, high T4, low or normal TSH) (14.3 vs 2.4%, p= 0.046) were more frequent in group I than group II. Male hypogonadism was also more prevalent in group I (75.6% vs 20.6%, p=0.006) than group II, with higher prevalence of both secondary (56.8 vs 15.3%, p=0.006) and primary (18.8 vs 5.3%, p=0.006) hypogonadism. Hyperprolactinemia was observed in 42.4% patients, without significant difference between both groups. Conclusion: COVID-19 can involve multiple endocrine organs and axes, with a greater prevalence and degree of endocrine dysfunction in those with more severe disease.